Studi Perbandingan Metode Resitasi Berbasis Daring Terhadap Hasil Belajar Matematika - Ardhia Pramesti, Ajeng; Rini, Juwita (Indonesian Journal of Islamic Elementary Education, 2021)
This study aims to determine whether the online-based recitation method can provide better student mathematics learning outcomes. The research approach used is a quantitative approach with a quasi-experimental type of research. The population and sample in this study were all students of fifth grade class in SDN Proyonanggan 01 Batang, totaling 47 students. The sample is divided into two classes, the control class is the class that does not use the online-based recitation method and the experimental class is the class that applies the online-based recitation method. Data collection techniques used are test and documentation methods. The test is used to measure students' mathematics learning outcomes and documentation is used to obtain documentary data. The data analysis technique in this study used an independent sample t test. The results of the study concluded that the online-based recitation method gave a better effect on the mathematics learning outcomes of fifth grade students at SDN Proyonanggan 01 Batang. This can be seen from the results of the independent sample t test, it is found that tcount= 3.182 > ttable= 2.014. These results mean that there is a significant difference in mathematics learning outcomes between the control class and the experimental class and the posttest average score for the experimental class is higher than the average score for the control class.